Organising Secretary’s Report on IX Annual Convention of SVSBT and National Seminar Organized at Veterinary College and Research Institute, Tirunelveli during 22, 23 & 24 September 2022 - ORGANISING SECRETARY’S REPORT (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The IX Annual Convention of the Society for Veterinary Science & Biotechnology (SVSBT) and National Seminar on “Recent Biotechnological Advances in Health and Management Practices to Augment Productivity of Livestock and Poultry”, was hosted by the Veterinary College and Research Institute, Tirunelveli, Tamilnadu - 627 358, a constituent unit of Tamil Nadu Veterinary and Animal Sciences University (TANUVAS), for three days from 22.09.2022 to 24.09.2022. A total of 188 delegates from all over India registered and participated in the National Seminar.